(untitled) (ІННОВАЦІЙНА ЕКОНОМІКА, 2024)
Савлук Р.Я., Вєрцева А.О. ІННОВАЦІЙНА ТРАНСФОРМАЦІЯ НАЦІОНАЛЬНОЇ ЕКОНОМІКИ: РЕГІОНАЛЬНІ, ГЛОБАЛЬНІ ТА ІНСТИТУЦІОНАЛЬНІ АСПЕКТИ Мета. Узагальнення сучасних тенденцій розвитку національної економіки, визначення факторів впливу на її динаміку та обґрунтування інструментів інституціонального впливу на інноваційну модернізацію. Методика дослідження. Теоретико-методологічною базою даного дослідження є системний підхід до визначення й узагальнення глобальних, регіональних, інституціональних і структурних факторів впливу на сучасний стан і тенденції розвитку національної економіки; структурно-функціональний аналіз макроекономічних тенденцій розвитку національного виробництва; інституціонально-еволюційний підхід до обґрунтування інструментарію регулювання інноваційного розвитку та активізації інноваційного процесу в економіці. Результати дослідження. Акцентовано, що мінімізувати негативні впливи глобальної динаміки, циклічні й соціально-політичні ризики здатна висока динаміка економічного зростання, що обумовлена станом і взаємодією базових факторів відтворення, які відповідні і адаптивні рівню досягнутого країною технологічного прогресу. Констатовано низьку частку експорту високотехнологічних товарів з національної економіки, що обумовлено низькою інноваційною активністю вітчизняних виробників, відсутністю передумов для інноваційного розвитку економіки, дефіцитом фінансування й низькою часткою витрат на НДДКР. Аргументовано, що забезпечення вищого рівня технологічності вітчизняного виробництва потребує підтримки й розвитку української науки та удосконалення моделі організації інноваційного процесу; реалізації фінансових програм підтримки інноваційного розвитку галузей та регіонів. Наукова новизна результатів дослідження. Обґрунтовано необхідність досягнення гармонійного поєднання рушійних сил модернізації (держава, ринок, суспільство) в реалізації стратегічного напряму розвитку соціально-економічної моделі. Аргументовано, що негативним впливам глобалізації, регіональним, соціально-політичним й економічним проблемам здатна протистояти інноваційна трансформація, що прискорює економічну динаміку; сприяє зростанню продуктивності виробництва, обсягів міжнародній торгівлі; адаптивності господарської системи до умов високих ризиків й несприятливих екзогенних змін. З огляду на стратегічний пріоритет реалізації інноваційної модернізації в національній економіці, інституціональна роль держави має бути реалізована за допомогою включення до формальних норм та діючих інститутів стимулів до інноваційної діяльності вітчизняних товаровиробників, а також шляхом формування інституціонального середовища, яке активізуватиме інноваційні трансформації. Практична значущість результатів дослідження. Теоретичні й методологічні положення дослідження поглиблюють практичні аспекти та інструментарій інституціонального регулювання інноваційної модернізації національної економіки і можуть виступати підґрунтям для подальших наукових розвідок. Ключові слова: інноваційна трансформація, інноваційна динаміка, інноваційний розвиток, глобалізація, регіоналізація, галузева структура, національна економіка, інтеграція, інститут, інституціональне регулювання, інституціональне забезпечення. Savluk R.Ya., Viertseva A.O. INNOVATIVE TRANSFORMATION OF THE NATIONAL ECONOMY: REGIONAL, GLOBAL AND INSTITUTIONAL ASPECTS Purpose. The aim of the article is to generalize the current trends in the development of the national economy, determine the influencing factors on its dynamics and substantiate the tools of institutional influence on innovative modernization. Methodology of research. The theoretical and methodological basis of this research is a systematic approach to the definition and generalization of global, regional, institutional and structural factors of influence on the current state and trends of the development of the national economy; structural and functional analysis of macroeconomic trends in the development of national production; an institutional-evolutionary approach to substantiating the toolset for regulation of innovative development and activation of the innovation process in the economy. Findings. It is emphasized that the minimizing the negative effects of global dynamics, cyclical, social and political risks can be achieved by the high dynamics of economic growth, which is determined by the state and interaction of the basic factors of reproduction, which are appropriate and adaptive to the level of technological progress achieved by the country. A low share of the export of high-tech goods from the national economy was established, which is due to the low innovative activity of domestic manufacturers, the lack of prerequisites for the innovative development of the economy, the lack of funding and the low share of R&D spending. It is argued that ensuring a higher level of technological efficiency of domestic production requires the support and development of Ukrainian science and improvement of the model of the organization of the innovation process; implementation of financial programs to support the innovative development of industries and regions. Originality. The need to achieve a harmonious combination of the driving forces of modernization (state, market, society) in the implementation of the strategic direction of the development of the social and economic model is substantiated. It is argued that the negative effects of globalization, regional, economic, social and political problems can be resisted by innovative transformation, which accelerates economic dynamics; contributes to the growth of production productivity, volumes of international trade; adaptability of the economic system to conditions of high risks and adverse exogenous changes. In view of the strategic priority of implementing innovative modernization in the national economy, the institutional role of the state should be implemented by including in formal norms and existing institutions incentives for the innovative activity of domestic product manufacturers, as well as by forming an institutional environment that will activate innovative transformations. Practical value. The theoretical and methodological provisions of the study deepen the practical aspects and tools of institutional regulation of innovative modernization of the national economy and can serve as a basis for further scientific research. Key words: innovative transformation, innovative dynamics, innovative development, globalization, regionalization, industry structure, national economy, integration, institute, institutional regulation, institutional support.